Penafsiran al-Qur’an dengan Media Konvensional - Yasif Maladi; Dadan Rusmana; Yayan Rahtikawati (UIN Sunan Gunung Djati Bandung, 2022)
The Qur'an is a guideline for Muslims; to understand it requires the science of interpretation; without interpretation, it will be difficult to understand the contents of the Qur'an. In its delivery, there are two essential things. First, it is related to understanding the meaning so that the message contained in it can be understood. Second, it relates to conveying the message so that it reaches Muslims. This research is literature research that seeks to re-examine the area of interpretation studies by taking the object of the phenomenon of practical interpretation of the Qur'an. The results of this study are conventional interpretation terminology, namely, conventional performance is identical to classical interpretation where there are several methods used in conventional interpretation, namely the tahlili, ijmali, muqorron and maudhui methods. Conventional interpretation cannot be separated from the study of the commentator and the method of interpretation studied.